Impact of treatment suspension on health-related quality of life in the EMBARK trial: a post hoc analysisResearch in context - Stephen J. Freedland; Ugo De Giorgi; Antti Rannikko; Fred Saad; Miguel Ramirez-Backhaus; Anchen F. Nasr; Jasmina I. Ivanova; Arijit Ganguli; Pavol Kral; Arlene L. Reisman; Neal D. Shore (EClinicalMedicine)
Summary: Background: Enzalutamide was approved for high-risk biochemically recurrent (hrBCR) prostate cancer based on the EMBARK trial (NCT02319837; 17 December 2014–31 January 2023). In EMBARK, treatment was suspended at week 37 if prostate-specific antigen (PSA) was <0.2 ng/mL and reinstated if PSA rose to ≥2.0 ng/mL with radical prostatectomy or ≥5.0 ng/mL without. This post hoc analysis assessed the impact of treatment suspension on health-related quality of life (HRQoL) to address overtreatment concerns. Methods: Longitudinal change in HRQoL from treatment suspension at week 37 to subsequent assessments until week 109 was analyzed with mixed models for repeated measures (MMRM) and descriptively among these patients. Separate models were used to assess four patient-reported outcome (PRO) instruments—Brief Pain Inventory – short form, Functional Assessment of Cancer Therapy – Prostate, QoL Questionnaire – Prostate 25, and European QoL 5-Dimensions 5-Levels health questionnaire—with predefined clinically meaningful thresholds. Intention-to-treat analysis was used. Findings: Treatment was suspended in 90% (321/355), 86% (304/355), and 67% (240/358) of participants treated with enzalutamide + leuprolide, enzalutamide monotherapy, and leuprolide alone, respectively. MMRM showed no meaningful change in any treatment arm after treatment suspension across all assessed PRO measures, except hormonal treatment-related symptoms, for which clinically meaningful improvement was observed after treatment suspension at week 61 for enzalutamide monotherapy, week 73 for leuprolide alone, and week 85 for enzalutamide + leuprolide. The descriptive analysis showed similar findings. Interpretation: Enzalutamide ± leuprolide in patients with hrBCR improves metastasis-free survival versus leuprolide alone with no clinically meaningful changes in the measured HRQoL domains during treatment or after treatment suspension, with gradual improvement in hormonal treatment-related symptoms after treatment suspension in this selective clinical trial population. Further real-world studies are warranted to better explore the benefits of treatment suspension. Funding: This study was funded by Pfizer Inc. and Astellas Pharma Inc.